Ranacang Bangun Sistem Keamanan Pada Jendela Dengan Jarak Jauh Menggunakan Sensor Kemiringan - Sutriandy . (Journal of Electrical Engineering, Energy, and Information Technology (J3EIT), 2015)
Abstract– Home security system currently required in society, this is intended to reduce the space for crime in the neighborhood. To create a home security system is needed tool tilt sensor as a detector slope, modems as media information delivery media remotely using SMS (short message service), buzzer as alarm for prevention/ give a warning, the LCD as a viewer condition and sets system minimum which using a microcontroller ATmega8, testing was applied with a miniature window in which when the window was open and there was slope on the sensor, the system will provide information to the owners and  activate the  alarm. From the  results of experiments conducted showed that showed that the tilt sensor can help monitor the condition of the windows with a remotely in real time and can be controlled by the user using mobile phone as the sender of the command.   Keywords – Microcontroller ATmega8, Tilt sensor, Wavecom Fastract M1306B, LCD (Liquid Crystal Dispplay).